Porcelain for the emperor : manufacture and technocracy in Qing China - Chen, Kai Jun (University of Washington Press, 2023)
"The exquisite ceramic ware produced at the Imperial Porcelain Manufactory at Jingdezhen in southern China functioned as a kind of visual propaganda for the Qing dynasty (1644-1911) court. Through a detailed study of porcelain manufacture loosely structured around the career of the Manchu bannerman Tang Ying, who supervised ceramic production for the emperor, this volume considers the role of specialist officials in producing the technological knowledge and distinctive artistic forms that were essential to cultural policies of the Chinese state. Through fiscal management, technical experimentation, and design, these imperial technocrats facilitated rationalized manufacturing in precapitalist and preindustrial society. The volume draws on first-hand archaeological evidence from Jingdezhen, the foremost site of porcelain manufacture, as well as the voluminous Archive of the Imperial Handicraft Workshops to investigate a regional factory, the imperial design system, technological treatises, experiments deployed in porcelain manufacture, and court regulations. Grounded in methods for studying science and technology in society, as well as literary and art history, it contributes to scholarship on global empires and on the history of science and technology in China. In describing how the imperial state's intervention in industry has left a lingering imprint on modern China through its labor-intensive modes of production, the division of domestic and foreign markets, and a technocratic culture of centralization, it provides a new perspective for understanding the technology behind goods "made in China.""--